Stress analysis of composite laminates - Liu, Shulong (2001)
A general displacement-based shear and transverse normal deformable plate theory is reviewed. Shear and transverse normal deformable plate theories suitable for cylindrical bending problems have been deduced from the general plate theory by introducing certain general functions of the transverse coordinate into the displacement field approximation. This theory takes into account the transverse shear and normal deformation effects and unifies most of the classical and shear deformable theories available in the literature.